A Review of Integrative Medicine in Gynaecological Oncology - Kalder, M.; Mueller, T.; Fischer, D.; Mueller, A.; Bader, W.; Beckmann, Matthias; Brucker, C.; Hack, Carolin; Hanf, V.; Hasenburg, A.; Hein, Alexander; Jud, Sebastian; et al. (Geburtshilfe und Frauenheilkunde, 2016)
In recent years complementary and alternative medicine (CAM) has increasingly been the focus of international research. Numerous subsidised trials (7903) and systematic reviews (651) have been published, and the evidence is starting to be integrated into treatment guidelines. However, due to insufficient evidence and/or insufficient good quality evidence, this has mostly not translated to practice recommendations in reviews by the Cochrane collaboration gynaecology group. There is nevertheless a not insignificant number of CAM providers and users. The percentage of oncology patients who use CAM varies between 5 and 90 %. Doctors have been identified as the main providers of CAM. Half of gynaecologists offer CAM because of personal conviction or on suggestion from colleagues. This must be viewed in a critical light, since CAM is mostly practiced without appropriate training, often without sufficient evidence for a given method - and where evidence exists, practice guidelines are lacking - and lack of safety or efficacy testing. The combination of patient demand and lucrativeness for doctors/alternative medicine practitioners, both based on supposed effectiveness CAM, often leads to its indiscriminate use with uncertain outcomes and significant cost for patients. On the other hand there is published, positive level I evidence for a number of CAM treatment forms. The aim of this article is therefore to review the available evidence for CAM in gynaecological oncology practice. The continued need for research is highlighted, as is the need to integrate practices supported by good evidence into conventional gynaecological oncology.
EVALuna2:32999